2022
DOI: 10.1155/2022/1924117
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Phenol onto Aluminum Oxide Nanoparticles: Performance Evaluation, Mechanism Exploration, and Principal Component Analysis (PCA) of Thermodynamics

Abstract: The removal of phenolic compounds from aqueous solutions using novel adsorption techniques becomes a key research item. Of those, nanoparticles in particular, the low-cost and the high-strength aluminum oxide nanoparticles showed promising results in pollutant uptake and increase in the adsorption efficiency. This study examined various physicochemical process parameters such as temperature, pH, initial phenol concentration, and adsorbent doses, in addition to the impact of those parameters on the adsorption r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Adsorption decreases slightly, and this may be due to the electrostatic repulsion interaction between the nano-sorbent and the adsorbate (negative charge holders). The achieved results agree with the previous literature's data 10 .
Figure 9 ( a ) Impact of the pH on removal efficiency for PHE, P-NP, and P-MP (Conditions: nano-sorbent dosage, PHE (0.20 g), P-NP, and P-MP (0.10 g), agitation time, 30 min; starting phenolic solutions concentration, 3 ppm; at 25 °C), and ( b ) Phenolate anions formation in aqueous media.
…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Adsorption decreases slightly, and this may be due to the electrostatic repulsion interaction between the nano-sorbent and the adsorbate (negative charge holders). The achieved results agree with the previous literature's data 10 .
Figure 9 ( a ) Impact of the pH on removal efficiency for PHE, P-NP, and P-MP (Conditions: nano-sorbent dosage, PHE (0.20 g), P-NP, and P-MP (0.10 g), agitation time, 30 min; starting phenolic solutions concentration, 3 ppm; at 25 °C), and ( b ) Phenolate anions formation in aqueous media.
…”
Section: Resultssupporting
confidence: 92%
“…In addition, it was observed that the adsorption capacity (amount) for PHE, P-NP, and P-MP were 9.72, 9.63, and 8.28 mg/g, respectively. The adsorption capacity remained constant as the nano-sorbent dosage decreased; this suggests a preference for using NPs as absorbent surfaces of target phenolic compounds 10 . Therefore, the nano-sorbent dosage was taken as 0.20 g of PHE, whereas 0.10 g of P-NP and P-MP in further experiments.…”
Section: Resultsmentioning
confidence: 93%
“…Although biological wastewater is considered the most widely used system to treat wastewater, it is not suitable for many industrial wastes that contain inhibitory substances for the growth of bacteria [1]. Therefore, adsorption is considered an vital process in industrial wastewater treatment and can be regarded as the most cost-effective and easy process for removing heavy metals from industrial wastewater [2,3]. Activated carbon has been the adsorbent extensively used over the past years.…”
Section: Extended Abstractmentioning
confidence: 99%
“…Substrate removal efficiencies, desalination efficiencies, and Coulombic efficiencies (CEs) were obtained, as described elsewhere (Ragab et al 2019a;Koomson et al 2022). To evaluate the relationship and variation between pH treatments, and to check the clusters and differences between them, a PCA and a cluster analysis were conducted using Minitab (Safwat et al 2022). The average values of duplicate cells were reported.…”
Section: Analysis Of Samplesmentioning
confidence: 99%